Cost-effectiveness analysis of pharmaceutical care in adult critically ill patients: based on a prospective cohort study - Wei, Chunyan; Hu, Ming; Chen, Guanghui; Yan, Zhijing; Yin, Wanhong; Wu, Zhiang (Frontiers in Pharmacology, 2024)
The medication regimen for critically ill patients is complex and dynamic, leading to a high incidence of drug-related problems. This study aimed to assess the effectiveness and economic efficiency of pharmaceutical care for these patients.In this prospective cohort study conducted in a tertiary hospital, adult patients were assigned either to a clinical pharmaceutical care group or a control group based on existing clinical grouping rules. Health outcomes and economic indicators were collected, followed by a cost-effectiveness analysis.The acceptance rate for clinical pharmacist interventions was 89.31%. The pharmaceutical care group exhibited significant reductions in the rate of medication errors (40.65% vs. 61.69%, P < 0.001) and adverse drug events (44.52% vs. 56.45%, P = 0.020). The usage rates for special-grade antibiotics (85.16% vs. 91.13%, P = 0.009) and proton pump inhibitors (77.42% vs. 88.71%, P = 0.002) were also lower in the pharmaceutical care group. Secondary outcomes did not show significant differences in total hospital stay (21 days vs. 22 days, P = 0.092). However, ICU stay was significantly shorter (9 days vs. 11 days, P = 0.003) in the pharmaceutical care group. Cost-effectiveness analysis demonstrated that each 1% reduction in adverse drug events associated with ICU pharmaceutical care saved $226.75 in ICU hospitalization costs and $203.42 in total ICU drug costs. A 1% reduction in the medication error rate saved $128.57 in ICU hospitalization costs and $115.34 in total ICU drug costs.Conclusions Pharmaceutical care significantly reduces adverse drug events and medication errors, promotes rational use of medications, decreases the length of ICU stay, and lowers treatment costs in critically ill patients, establishing a definitive advantage in terms of cost-effectiveness.